Verifying tumor position during stereotactic body radiation therapy delivery using (limited-arc) cone beam computed tomography imaging. Issue 3 (June 2017) - Hazelaar, Colien; Dahele, Max; Scheib, Stefan; Slotman, Ben J.; Verbakel, Wilko F.A.R.
Abstract: Background and purpose: Proof of tumor position during stereotactic body radiotherapy (SBRT) delivery is desirable. We investigated if cone-beam CT (CBCT) scans reconstructed from (collimated) fluoroscopic kV images acquired during irradiation could show the dominant tumor position. Materials and methods: Full-arc CBCT scans were reconstructed using FDK filtered back projection from 38 kV fluoroscopy datasets (16 patients) continuously acquired during volumetric modulated spine SBRT. CBCT-CT match values were compared to the average spine offset values found using template matching + triangulation of the individual kV images. Multiple limited-arc CBCTs were reconstructed from fluoroscopic images acquired during lung SBRT of an anthropomorphic thorax phantom using 20–180° arc lengths and for 3 breath-hold lung SBRT patients. Results: Differences between 3D CBCT-CT match results and average spine offsets found using template matching + triangulation were 0.1 ± 0.1 mm for all directions (range: 0.0–0.5 mm). For limited-arc CBCTs of the thorax phantom, the automatic 3D CBCT-CT match results for arc lengths of 80–180° were ≤1 mm. 20° CBCT reconstruction still allowed for positional verification in 2D. Conclusions: (Limited-arc) CBCT reconstructions of kV images acquired during irradiation can identify the dominant position of the tumor during treatment delivery.